Aseptic process validation of [18F]Sodium Fluoride radiopharmaceutical in-house production - Atanasova Lazareva, Marija; Kolevska, Katerina; Chochevska, Maja; Velichkovska, Maja; Janevikj Ivanovska, Emilija; Jolevski, Filip; Ugrinska, Ana (Macedonian Pharmaceutical Association, Ss. Cyril and Methodius University in Skopje, Faculty of Pharmacy, 2003)
Sodium fluoride ([18F]NaF) is a PET radiopharmaceutical for vizualization of the skeletal system and microcalcification. In the originally designed in-house method, [18F]NaF is recovered in aqueous solution after cyclotron irradiation, sterilized by passage through a 0.22 µm sterile filter and dispensed under aseptic conditions. To ensure the microbiological safety of drugs produced under aseptic conditions, validation of aseptic procedures is always recommended. This is essential for radiopharmaceuticals because most of them are released for administration before any sterility test can be completed due to their radioactive nature. This study reports the validation of the aseptic process applied to the internal production of [18F]NaF carried out in two phases: testing the number of viable microorganisms in radiopharmaceutical product prior to sterilization and process simulation studies (media fill tests). We found that all samples were sterile and the endotoxin concentration was well below the maximum acceptable level reported in the Ph Eur. monograph on [18F]NaF. The results confirmed that the entire production process of [18F]NaF can be carried out under strictly aseptic conditions following the validated procedures preserving the sterility of the final product.
Keywords: [18F]NaF; radiopharmaceutical; validation; aseptic process